Gel properties of grass carp myofibrillar protein modified by low-frequency magnetic field during two-stage water bath heating. (October 2020) - Wang, Limei; Xia, Minquan; Zhou, Yuanhua; Wang, Xian; Ma, Jing; Xiong, Guangquan; Wang, Lan; Wang, Shaojin; Sun, Weiqing
Abstract: The effects of low-frequency magnetic field (LF-MF) on the gel properties of grass carp myofibrillar proteins (GCMPs) and the underlying mechanisms were investigated to explore a better processing method for surimi gel products. GCMPs were untreated or treated with LF-MF of 9.5 mT in the first stage (40 °C heating for 50 min) or the second stage (85 °C heating for 40 min) of two-stage water bath heating. Results indicated that in the first stage, LF-MF induction may be detrimental to GCMPs unfolding and possibly resulted in a poor and unstable the GCMPs gels network structure, which had a negative effect on gel strength. Hence, water easily leaked from the GCMPs gel, leading to a decrease in WHC. Inversely, the unfolding of α-helix and the formation of random coil of LF-MF treatment in the second stage resulted in more exposure of internal groups, leading to the reduction of ionic bonds and increase of hydrogen bonds. These changed bonds further affected the T21 relaxation time, increased in PT2b and decreased in PT22, and mainly impacted the bind between water and protein, thus resulting in the improved gel strength and WHC. Graphical abstract: Image 1 Highlights: Gel strength and WHC increased at 9.5 mT (magnetic field) in the second stage. 9.5 mT treatment reduced T21 of GCMPs (grass crap myofibrillar proteins) gel. Unfolding of α-helix at 9.5 mT in the second stage favored increase of juiciness. A compact and dense network structure was obtained at 9.5 mT in the second stage. 9.5 mT treatment in the second stage leaded to reduction of ionic bonds.